Da'wah Strategy of Nurul Hikmah Islamic Boarding School in Instilling Islamic Values of the People of Cinta Manis Baru Village, Air Beetle District - Madeni Madeni (CV. Syntax Corporation Indonesia, 2023)
Research Objectives: The purpose of this research is to find out how the Da'wah Strategy of Nurul Hikmah Islamic Boarding School in Instilling Islamic Values in the Community of Cinta Manis Baru Village, Air Beetle District, Research Method: the method used in this study is to use qualitative methods using interactive model data analysis techniques (Interactive Model) in the Miles and Huberman theory model which has three components including: Data Reduction, Presentation of data (Data Display), and drawing and testing conclusions or verification (Conclusion Drawing. Conclusion: This study concludes that Nurul Hikmah Islamic Boarding School has a significant role in improving the quality of human resources and building Islamic awareness in Cinta Manis Baru Village. The efforts of Islamic boarding schools in organizing educational activities, community guidance, and economic organizing through BMT Bina Umat contribute to changing people's views and behaviors towards a more Islamic life.